Kesadaran Masyarakat dalam Membayar Zakat Fitrah di RT 05 Dusun Nglorog, Desa Mojopuro, Kecamatan Jatiroto, Wonogiri - Meidiana Safitri; Harianti Fauziyatul Izah; Muhamad Ridho; Fauzun Jamal (Jurnal Pelayanan Masyarakat, 2025)
Zakat Fitrah is one of the obligations in Islam aimed at purifying the soul and strengthening social solidarity among Muslims. This study aims to analyze the level of public awareness in paying Zakat Fitrah in RT 05, Ngolorog Hamlet, Mojopuro Village, Jatiroto Subdistrict, Wonogiri Regency. The method used includes in-depth interviews with community leaders and field observations. The results show that residents have a high level of awareness regarding the obligation of Zakat Fitrah, yet there are still obstacles such as a lack of understanding of the procedures for payment and distribution. Factors such as education, income, and socialization by religious leaders play a significant role in enhancing awareness. The conclusion of this study recommends improving educational programs and zakat campaigns by the village government and religious institutions to encourage better compliance, thereby contributing to social welfare in the area. This research is expected to serve as a reference for developing zakat programs in rural regions.